Strategy for Developing Fisheries Sme’s Based on Processed Milk and Seaweed Using Electric Shock Pasteurization Tecnology - Zainal Abidin; Eko Waluyo; Wahyu S. Utomo (Faculty of Fisheries and Marine Science, Brawijaya University, 2018)
Seaweed is one of the leading aquaculture commodities. Seaweed contains many enzymes and fiber that are good for health. So that the selling value of seaweed does not fall, for example, the SME’s Poklahsar